A Study on some Properties of Fourier Integrals Based on Neutrosophic Function - Prasen Boro; Bhimraj Basumatary (Neutrosophic Sets and Systems)
Fourier transforms is one of the oldest and a well-known technique in field of mathematic and engineer ing mathematical work. Fourier transform method represents the variable as a summation of complex exponentials. Fourier analysis has been used in signal processing and digital image processing for the analysis of a single image as a two-dimensional wave form, and many other type of form like Quantum mechanics, Signal processing, Image Pro cessing. This analysis also represents filters, Transformation, representation, and encoding, Data Processing, Analysis and many more fields. In this article, some basics of Fourier Integrals have been discussed in terms of neutrosophic set. Dirichlet’s Conditions, Fourier integral formula and it’s five different forms are studied based on neutrosophic set. This article includes the F.T., F.S.T. and F.C.T. of a neutrosophic function and their inversion formulae. In this study, some properties of F.T. are discussed for a neutrosophic function. This study will help to get better results in signal processing, image processing, and in other fields also. This serves as an overview of the Fourier integral of a neutrosophic function.